2014
DOI: 10.1519/jsc.0000000000000469
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Compression Garments on Recovery After Marathon Running

Abstract: Strenuous physical activity can result in exercise-induced muscle damage. The purpose of this study was to investigate the efficacy of a lower limb compression garment in accelerating recovery from a marathon run. Twenty four subjects (female, n = 7; male, n = 17) completed a marathon run before being assigned to a treatment group or a sham treatment group. The treatment group wore lower limb compression tights for 72 hours after the marathon run, the sham treatment group received a single treatment of 15 minu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
80
0
3

Year Published

2016
2016
2017
2017

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 57 publications
(93 citation statements)
references
References 27 publications
10
80
0
3
Order By: Relevance
“…These findings are consistent with existing literature which suggests that resistance exercise typically leads to greater levels of muscle damage than running [65][66][67], while non-load bearing exercise is subject to even less eccentric load [12]. Although running can result in comparable levels of EIMD to resistance exercise, for example, following a marathon [21], levels of EIMD reported throughout the literature are generally lower than those from resistance training [68].…”
Section: Compression Muscle Damage and Strength Recoverysupporting
confidence: 88%
See 4 more Smart Citations
“…These findings are consistent with existing literature which suggests that resistance exercise typically leads to greater levels of muscle damage than running [65][66][67], while non-load bearing exercise is subject to even less eccentric load [12]. Although running can result in comparable levels of EIMD to resistance exercise, for example, following a marathon [21], levels of EIMD reported throughout the literature are generally lower than those from resistance training [68].…”
Section: Compression Muscle Damage and Strength Recoverysupporting
confidence: 88%
“…Whilst previous analyses have reported a tendency for CG to exert greater relative effects on power recovery [9,64], these analyses were less extensive. Hill et al [21] reported a tendency towards larger effects for power recovery compared to strength, following the analysis of 17 power outcomes from six studies and 16 strength outcomes from five studies (a total of eight studies and 33 data-points). Similarly, Marques-Jimenez et al [64] recently reported a tendency towards comparatively greater effects on power recovery after analysing 30 power outcomes from five studies and 45 strength outcomes from eight studies (nine studies and 75 data-points in total).…”
Section: Performance Outcomesmentioning
confidence: 99%
See 3 more Smart Citations